Investigation of the effect of EDM parameters on dimensional accuracy of drilled holes of 304 stainless steel using RSM method - Hanash, Ebrahim Abdullah Hasan (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
The current demand of miniaturized parts with high quality output is growing rapidly due to the fast development of technology in all fields such as aerospace, automotive, medical, biomedical and electronic industry. Besides that, machining operation is the pre-requisite of any manufacturing process for shaping different parts and components. Therefore, this study presents general overview of the main categories of the machining operations and the main study is on the electrical discharge machining (EDM) specifically ED-Drilling. The EDM processes have the abilities to do machining hard materials which have applications in many industries. It is made possible by EDM because of the absence of the direct contact between the cutting tool (electrode) and the work materials unlike the conventional machining processes. Even though, ED-Drilling can cut hard materials, however, some characteristics such as material removal rate (MRR), electrode wear rate (EWR), surface roughness (SR), overcut (OC), circularity and taper angle should be investigated to find the optimal parameters to produce good quality holes. In this study, overcut and taper angle are investigated in machining of stainless steel 304, against three different parameters such as electric current, pulse on time (Ton) and pulse off time (Toff). The hole diameter was 1 mm with aspect ratio of 10. Dimensional accuracy was measured by evaluating the overcut and the taper angle. These two measurements were performed using optical microscope. The experimentation planning, evaluation, analysis and optimization have been carried out on DOE software version 10.0.3 based on RSM method. The research can be done on higher aspect ratio to study the behaviour. The research reveals that, discharge current was found to be the most significant factor affecting the overcut and the taper angle followed by pulse on time and pulse off time. As the discharge current and pulse on time increase, the overcut and taper angle are increased. In the case of the pulse off time, as it increases, the overcut and taper angle decreases. The optimized parameters that give the minimum overcut and taper angle response are 9 A current, 30 µs Pulse on time and 35 µs Pulse off time which gives 0.010 mm overcut and 0.244° taper angle. The validation of the model has been performed with percentage error of less than 5%.